2012
DOI: 10.1186/2193-1801-1-77
|View full text |Cite
|
Sign up to set email alerts
|

Screening of recombinant proteins as antigens in indirect ELISA for diagnosis of bovine tuberculosis

Abstract: Bovine tuberculosis is an important infectious disease caused by Mycobacterium bovis, which is responsible for considerable economic losses. This disease constitutes a serious public health problem. Control programs in most countries, including Brazil, are based on the identification and slaughter of infected animals, as defined by the skin tuberculin test, which has its constraints. In the present study, the recombinant proteins CFP-10, ESAT-6, Mb0143, MPB83, PE5, PE13, TB10.4, TB15.3 and a chimera of ESAT-6/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…and 75.5-98.0%, respectively [12,22,25,26]. In this study, rM70S showed higher or equivalent sensitivity and specificity than those in previous studies.…”
Section: Discussionmentioning
confidence: 49%
“…and 75.5-98.0%, respectively [12,22,25,26]. In this study, rM70S showed higher or equivalent sensitivity and specificity than those in previous studies.…”
Section: Discussionmentioning
confidence: 49%
“…Os genes pe5, pe13 e esat-6 foram amplificados por reação em cadeia da polimerase (PCR) a partir de DNA de M. bovis cepa AN5, utilizando oligonucleotídeos iniciadores específicos desenhados e amplificados de acordo com Souza et al (2012). O gene esx-1 foi amplificado com os primers (forward: 5' TATCAATTCGGGGACGTCGACGCTCACG 3' e reverse: 5' GGCGCTGTCGGTTTGTGCCATGTTGTTG 3') desenhados utilizando o programa PrimerSelect (DNASTAR).…”
Section: Methodsunclassified
“…All recombinant proteins used in this study were previously evaluated in ELISA as described by Souza et al (2012) and were recognised by antibodies (IgG) of cattle naturally infected with M. bovis.…”
Section: Gene Cloning Production and Evaluation Of Recombinant Proteinsmentioning
confidence: 99%
“…The animals came from a herd with no clinical or pathological history of tuberculosis during the last 3 years, as evidenced by inspection at slaughter. In addition, all the animals used were negative in ELISA based on MPB70 and P27 recombinant antigens, according to Farias et al (2012). Twenty-four animals were sensitised by subcutaneous injection of 10 mg of inactivated heat (96-105 °C for 30 min) M. bovis AN5 strain, which was supplied by the LANAGRO/ Brazilian Ministry of Agriculture (Pedro Leopoldo, Brazil) to simulate the immunological response observed in M. bovis infected animals.…”
Section: Cattle Sensitisationmentioning
confidence: 99%
See 1 more Smart Citation